Biocompatibility, Biomineralization and Induction of Collagen Maturation with the Use of Calcium Hydroxide and Iodoform Intracanal Dressing - Bueno, Carlos Roberto Emerenciano [UNESP]; Sarmiento, Jimena Lama [UNESP]; Vasques, Ana Maria Veiga [UNESP]; da Silva, Ana Cláudia Rodrigues [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Santos, João Miguel Marques; Dezan-Júnior, Eloi [UNESP] (MDPI, 2023)
Biocompatibility and biomineralization of root canal dressings are important requirements for periapical healing. This study evaluated the inflammatory response, biomineralization and tissue repair by collagen fiber maturation in the subcutaneous tissue of rats. Eighteen Wistar rats (n = 6) received subcutaneous implants: calcium hydroxide + propylene glycol [CH+P], calcium hydroxide + propylene glycol + iodoform [CH+P+I], iodoform + carbowax [I+Cwax] and carbowax [Cwax]. Extra empty tubes were used as a control [C]. After 7, 15 and 30 days, the implants were removed with surrounding tissue for staining of hematoxylin-eosin, Von Kossa, picrosirius red and without staining for analysis under polarized light. Results were analyzed via Kruskal–Wallis followed by Dunn testing for nonparametric data and ANOVA followed by a Tukey post hoc test for parametric data (p < 5%). At 7 days, all groups showed a moderate inflammatory reaction and thick fibrous capsule, except the [Cwax] group, with a severe inflammatory infiltrate (p < 0.05). After 15 days, all groups but control had a decrease in inflammatory response. At 30 days, all groups presented a mild reaction and thin fibrous capsule (p > 0.05). Only groups containing calcium hydroxide were found to be positive using Von Kossa staining and polarized light in all periods. At 7 days, all groups showed a higher proportion of immature fibers. At 15 days, the [CH+P] and [Cwax] groups increased their proportion of mature/immature fibers. At 30 days, only the [CH+P] group presented a significant prevalence of mature collagen fibers (p < 0.05). All groups showed biocompatibility, but only groups containing calcium hydroxide induced biomineralization. The addition of iodoform delayed tissue healing.
Keywords: calcium hydroxide; collagen; endodontics; inflammation; intracanal dressing; iodoform